The Existence of Solutions for a Nonlinear Fractional Multi-Point Boundary Value Problem at Resonance - Xiaoling Han; Ting Wang (International Journal of Differential Equations)
We discuss the existence of solution for a multipoint boundary value problem of fractional differential equation. An existence result is obtained with the use of the coincidence degree theory.